A Long Relationship With Diabetes Mellitus With The Incidence Of Sexual Dysfunction In The Working Area Of The Tilongkabila Health Center - Veliyanti H. Kadir; Ita Sulistiani Basir; Gusti Pandi Liputo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Diabetes Mellitus (DM) is a chronic disease that can cause various complications, one of which is sexual dysfunction. The length of suffering from DM is suspected to play a role in increasing the risk of sexual dysfunction due to progressive nerve and blood vessel damage. This study aims to determine the relationship between the length of time suffering from Diabetes Mellitus and the incidence of sexual dysfunction in the working area of the Tilongkabila Health Center, Bone Bolango Regency. This study uses a correlational descriptive design with a cross-sectional approach. The study population was 278 DM patients, with a sample of 74 respondents selected using the Proportionate Stratified Random Sampling technique. Data was collected through questionnaires and analyzed using the Chi-Square test. The results showed that most of the respondents had suffered from DM for more than 5 years as many as 44 people (59.5%) and experienced indications of sexual dysfunction as many as 69 people (93.2%). The results of the statistical test showed a p-value of 0.151 (p>0.05), which means that there was no significant relationship between the length of time of suffering from Diabetes Mellitus and the incidence of sexual dysfunction. Although theoretically a longer duration of the disease can increase the risk of sexual complications, the results of this study show that the incidence of sexual dysfunction in DM patients is multifactorial and is influenced by various other factors such as age, psychological condition, lifestyle, and blood sugar level control. Therefore, a comprehensive approach is needed in the prevention and treatment of sexual dysfunction in Diabetes Mellitus patients.